Endoplasmic Reticulum Stress–Induced Cell Death in Dopaminergic Cells: Effect of Resveratrol - Chinta, Shankar J. (2009)
Resveratrol, a naturally occurring polyphenol, exhibits antioxidant, antiaging, and anticancer activity. Resveratrol has also been shown to inhibit tumor initiation, promotion, and progression in a variety of cell culture systems. Earlier, we showed that paraquat, a bipyridyl herbicide, triggers endoplasmic reticulum stress, cell dysfunction, and dopaminergic cell death. Due to its antioxidant activity, we assessed the ability of resveratrol to rescue cells from the toxic effects of paraquat. While resveratrol did not have any protective effect at low concentrations, it triggered endoplasmic reticulum (ER) stress-induced cell death at higher concentrations (50–250 µM). The present study was carried out to determine the mechanism by which resveratrol triggers ER stress and cell death in dopaminergic N27 cells. Our studies demonstrate that resveratrol triggers ER stress and cell dysfunction, caspase activation, p23 cleavage and inhibition of proteasomal activity in dopaminergic N27 cells. While over expression of uncleavable p23 was associated with decreased cell death, down-regulation of p23 protein expression by siRNA resulted in enhancement of ER stress-induced cell death triggered by resveratrol indicating a protective role for the small co-chaperone p23 in dopaminergic cell death.